Cardiac safety assessment of a novel recombinant bispecific antibody targeting the ether-à-go-go related gene 1 (hERG1)-β1 integrin macromolecular complex - Santini, Lorenzo; Duranti, Claudia; Palandri, Chiara; Giammarino, Lucrezia; Musumeci, Monica; Carlucci, Lucia; Capitani, Chiara; Colasurdo, Rossella; Recchia, Fabio; Cerbai, Elisabetta; Coppini, Raffaele; Arcangeli, Annarosa (Frontiers in Pharmacology, 2023)
In the last decades, mounting evidence has pointed out the human ether-á-go-go-related gene (hERG1) potassium channel as a novel biomarker in human cancers. However, hERG1 sustains the cardiac repolarizing current IKr and its blockade can induce a prolonged QT interval at the ECG, which increases the risk of life-threatening arrhythmias. This represents a major hindrance for targeting hERG1 for antineoplastic therapeutic purposes. Based on our discovery that hERG1 resides in a macromolecular complex with the β1 subunit of integrin adhesion receptors only in tumors, and not in the heart, we generated (and patented WO2019/015936) a novel engineered, single chain, bispecific antibody in the format of a diabody (scDb-hERG1-1). This antibody has been proven to target with high affinity the hERG1/β1 integrin complex and to exert a good antineoplastic activity in preclinical mouse models. In the present study, we evaluated the cardiac safety of the scDb-hERG1-1, determining the action potential duration (APD) of human cardiomyocytes, either atrial (from valvedisease patients) or ventricular (from aortic stenosis patients). Cardiac cells were incubated in vitro with (i) the scDb-hERG1-1, (ii) the full length anti-hERG1 monoclonal antibody (mAb-hERG1) and (iii) its single chain Fragment variable derivative (scFv-hERG1), from which the scDb-hERG1-1 was assembled. All the tests were performed before and after treatment with the specific hERG1 blocker E4031. In addition, we have performed preliminary experiments, analyzing the effects of the scDb-This is a provisional file, not the final typeset article hERG1/1 in vivo measuring the QT interval length of the surface ECG after its injection intravenously in farm-pigs.The scDb-hERG1-1 did not produce any lengthening of APD compared to control (vehicle) conditions, either in atrial or ventricular cardiomyocytes, whereas both the hERG1-mAb and the scFv-hERG1 produced a significant APD prolongation. The addition of E4031 further prolonged APD. The scDb-hERG1-1 did not produce any alterations of the QT (and QTc) interval values, once injected intravenously in farm pigs. Overall, the above evidences plead for the cardiac safety of the scDb-hERG1-1, suggesting that an application of this antibody for anti-cancer therapy will be untainted by cardiotoxicity.